Dartos Fascia as an Interpositional Layer in Hypospadias Urethroplasty: A Systematic Review - Marta Hendry; Krisna Murti; Besut Daryanto; Iche Andriyani Liberty (Green Publisher Indonesia, 2025)
This systematic review evaluated the role of dartos fascia as an interpositional layer in primary hypospadias repair. Search was conducted in PubMed, EMBASE, Scopus, CENTRAL, and Web of Science (2019–2025) for studies in patients ≤18 years undergoing hypospadias repair. Primary outcomes were urethrocutaneous fistula (UCF), dehiscence, meatal/urethral stenosis, and reoperation; secondary outcomes were infection and cosmetic scores. Narrative synthesis was used. Results: Eleven studies met criteria, predominantly distal TIP. No randomized trial compared any second layer versus none; one cohort (n=425) showed similar UCF with periurethral/dartos coverage versus none (6.7% vs 7.3%). A randomized trial favored double- over single-layer dartos (3.3% vs 23.3%). Another trial found ventral preferable to dorsal dartos with fewer flap-related complications at similar UCF rates. Tunica vaginalis flap reduced UCF and improved cosmetics but is more invasive. Platelet-rich fibrin adjunct lowered UCF and infection in two studies. Spongioplasty produced comparable UCF but higher meatal stenosis, though selected robust spongiosum allowed zero fistulas. Conclusion: Dartos remains the workhorse; double-layer and ventral harvest optimize outcomes, while tunica vaginalis and PRF offer effective alternatives in selected cases. Further randomized trials are needed to clarify the necessity of a second layer.